2017
DOI: 10.2147/ppa.s148099
|View full text |Cite
|
Sign up to set email alerts
|

Positive airway pressure adherence and subthreshold adherence in posttraumatic stress disorder patients with comorbid sleep apnea

Abstract: Study objectivesPatients with comorbid posttraumatic stress disorder (PTSD) and obstructive sleep apnea (OSA) manifest low adherence to continuous positive airway pressure (CPAP) due to fixed, pressure-induced expiratory pressure intolerance (EPI), a subjective symptom and objective sign aggravated by anxiety sensitivity and somatosensory amplification. As advanced PAP therapy modes (ie, auto-bilevel PAP [ABPAP] or adaptive servo-ventilation [ASV]) may address these side effects, we hypothesized such treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…More precise knowledge is needed regarding the effects of pharmaceutical treatments, which will enable the formulation of more precise recommendations. Furthermore, RCTs should be developed to explore how PAP therapy provides clinical improvement in nightmare disorder (Bahammam et al., ; Krakow et al., ), especially against the background that many patients do not tolerate PAP therapy (Jaoude et al., ); nonetheless, a recent study showed higher than usual adherence rates in PTSD patients using advanced PAP modes such as auto‐bilevel or adaptive servo‐ventilation (Krakow, Obando, Ulibarri, & Mciver, ). Furthermore, the possibilities of lucid dreaming as treatment deserve more attention.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…More precise knowledge is needed regarding the effects of pharmaceutical treatments, which will enable the formulation of more precise recommendations. Furthermore, RCTs should be developed to explore how PAP therapy provides clinical improvement in nightmare disorder (Bahammam et al., ; Krakow et al., ), especially against the background that many patients do not tolerate PAP therapy (Jaoude et al., ); nonetheless, a recent study showed higher than usual adherence rates in PTSD patients using advanced PAP modes such as auto‐bilevel or adaptive servo‐ventilation (Krakow, Obando, Ulibarri, & Mciver, ). Furthermore, the possibilities of lucid dreaming as treatment deserve more attention.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Since 2008, compared to CPAP, we have noted that ABPAP or ASV devices have a much greater ability to smooth the airflow curve [37] on both inspiration and expiration, the latter among patients meeting complex sleep apnea diagnosis (central apnea index (CAI) > 5; CAI/AHI > 50%). In fact, we recently demonstrated higher than usual adherence rates (58%) in PTSD patients using these advanced PAP modes [38] in contrast to commonly reported lower compliance rates (~ 30%) [39] in this vulnerable population. Therefore, we have speculated that a major advantage of ASV or ABPAP over CPAP is the capacity for advanced modes to prevent or eradicate EPI, a principal cause of CPAP rejection [40, 41].…”
Section: Introductionmentioning
confidence: 90%
“…In a recently published study, we describe our use of advanced PAP therapy devices in PTSD patients who often fail the fixed CPAP mode of treatment primarily due to expiratory pressure intolerance (EPI) or iatrogenic central apneas or both [38]. Many patients fail at initial exposure during the titration itself or even earlier during the desensitization procedure conducted at the presleep portion of overnight polysomnography [46, 47].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reductions in SI and depression, mental health issues commonly comorbid with PTSD, were noted after 3 months of PAP 27 . Unfortunately, poor adherence to PAP is a well‐documented problem in both civilian and veteran populations, with partial use of PAP more common in patients with a psychiatric comorbidity than among the general population 28 . Studies of regular PAP use in active duty military patients and veterans with OSA report that only 25% to 41% of patients with PTSD used PAP regularly compared to 58% to 70% of those without PTSD 21,26,29,30 , with reported reasons for nonadherence including mask discomfort, claustrophobia, and air hunger 29 .…”
Section: Introductionmentioning
confidence: 99%